Commercialization of graphene-based technologies: a critical insight. Issue 33 (28th April 2015) - Ciriminna, Rosaria; Zhang, Nan; Yang, Min-Quan; Meneguzzo, Francesco; Xu, Yi-Jun; Pagliaro, Mario
<x xml:space="preserve">Abstract</x> New methods to exfoliate graphite open the route to massive adoption of graphene as the enabler of important technologies, including enhanced electricity storage.